A grounded theory study for digital academic entrepreneurship. Issue 7 (26th February 2020) - Toniolo, Korinzia; Masiero, Eleonora; Massaro, Maurizio; Bagnoli, Carlo
Abstract : Purpose: This research aims to investigate how digital academic entrepreneurship (AE) develops, exploring its evolution from a micro to a macro perspective and highlighting the role of intellectual capital along the process. This paper contributes to the Special Issue on digital AE, providing research and practical implications. Design/methodology/approach: This study adopts a grounded theory approach which allows exploring the "How" question of digital AE. It focuses on the case of "Strategy Innovation, " the Ca' Foscari University of Venice (Italy) spin-off. Findings: Digital AE develops and regenerates through a virtuous cycle that, while supported by digital technologies, starts from single individuals and their networks, reaches a broader ecosystem, and ends once back to individuals. This study offers insights about the social impact of academic venturing activities and provides practitioners with useful insights for the understanding of academic spin-offs activities and related opportunities. Research limitations/implications: This study focuses on the specific research context of "Strategy Innovation, " Ca' Foscari University of Venice (Italy) spin-off. Future research should address in-depth analyses in the exploration of how digital AE emerges and evolves in different contexts and forms. Originality/value: This study investigates digital AE's development over time, broadly illustrating the phenomenon from a micro to a macro perspective and presenting an explicative and analytical model.